2021
DOI: 10.1186/s13690-021-00749-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic syndrome prevalence using four different definitions – a population-based study in Finland

Abstract: Background Metabolic syndrome (MetS) is a public health problem in Europe, affecting all age groups. Several MetS definitions are available. The aim of this study was to compare four different MetS definitions in the Finnish adult population, to assess their agreement and to evaluate the impact of the choice of the definition on the prevalence of MetS. Methods Data from FinHealth 2017, a cross-sectional national population health survey, focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
3
23
0
Order By: Relevance
“…We also performed a sensitivity analysis using the International Diabetes Federation (IDF) criteria. This definition requires an increased WC (for men ≥94 cm and for women ≥80 cm) plus at least two of the following 42 : (1) FPG ≥ 5.6 mmol/L or previous diagnosis of T2DM, (2) TG ≥ 1.70 mmol/L or current use of antihyperlipidemic medication, (3) HDL‐C < 1.04 mmol/L for men and <1.30 mmol/L for women, and (4) SBP ≥ 130 mm Hg or DBP ≥ 85 mm Hg or current use of antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed a sensitivity analysis using the International Diabetes Federation (IDF) criteria. This definition requires an increased WC (for men ≥94 cm and for women ≥80 cm) plus at least two of the following 42 : (1) FPG ≥ 5.6 mmol/L or previous diagnosis of T2DM, (2) TG ≥ 1.70 mmol/L or current use of antihyperlipidemic medication, (3) HDL‐C < 1.04 mmol/L for men and <1.30 mmol/L for women, and (4) SBP ≥ 130 mm Hg or DBP ≥ 85 mm Hg or current use of antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
“…We also performed a sensitivity analysis using the International Diabetes Federation (IDF) criteria. This definition requires an increased WC (for men ≥94 cm and for women ≥80 cm) plus at least two of the following 42…”
Section: Classification and Definitionmentioning
confidence: 99%
“…Males (69) have a higher prevalence of BP than females (61.5%) in NCEP ATP III and in IDF prevalence also, males (76.9%) are higher than females (48.4%). Haverinen et al found the same study in Finland [67]. An association between MetSs with biochemical components is presented in Table 12.…”
Section: Rajwal Et Almentioning
confidence: 61%
“…Metabolic syndrome is an increasingly important global public health issue affecting both developed and developing nations [1][2][3][4]. The studies revealed 34.1%, 33.3%, 21.66%, 37.05%, 19.1%, 43.83%, 20.6% and 34.2% burden of MetS in Brazil [5], Finland [6], Indonesia [7], Iran [8], Uganda [9], Ghana [10], Malaysia [11], and Ethiopia [12], respectively. According to ATP III guideline [13], MetS is defined as the presence of three or more of the following conditions: waist circumference(WC) �102 cm in men or �88 cm in women; blood pressure (BP) �130/ �85 mm Hg; fasting blood glucose (FBS) �126 mg/dl; triglyceride (TG) �150 mg/dl and low high-density lipoprotein (HDL) <40 mg/dl in men or <50 mg/dl in women.…”
Section: Introductionmentioning
confidence: 99%